2022
DOI: 10.3389/fpsyg.2022.850614
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Pre-Olympic Athletes’ Motivations and Barriers to Pursuing Dual Career as a Function of Sociodemographic, Sport and Academic Variables

Abstract: The dual career allows elite athletes to attain their maximum competitive and academic performance, but the COVID-19 pandemic hindered their development and changed their perception of the importance given to the sporting and educational environment. For this reason, the aim of the present study was to determine the differences in the motivations and perceived barriers, the importance given to academic qualifications, and the perception of the dual career from a multifactorial perspective, of elite athletes ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…Previous studies investigated the subjective perception of student-athletes regarding their dual career barriers and services at university level [ 16 , 39 ]. Undoubtedly, being the final recipients of policies and services for dual career, the student-athletes’ point of view is crucial for recognizing problems and foreseeing solutions for building a dual career-supporting environment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigated the subjective perception of student-athletes regarding their dual career barriers and services at university level [ 16 , 39 ]. Undoubtedly, being the final recipients of policies and services for dual career, the student-athletes’ point of view is crucial for recognizing problems and foreseeing solutions for building a dual career-supporting environment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that student-athletes, with a dual career, report symptoms of sports and / or academic burnout early in secondary school (e.g., Felix-Mena et al, [6]; Gustafsson et al, [10]; Sorkkila et al, [7]). Furthermore, burnout appears to be associated with school and sports dropout, with students with burnout being four times more likely to drop out of school than students without burnout [11,9,7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These results may be linked to the specific character of each sport. Since, for example, in individual sport, the athlete is responsible for the necessary strategy to guarantee its own success, and in the team, sports athletes must work together for success [11]. With regard to NCT, it was found that women, compared to boys, tend to have more pessimistic thoughts about their careers, which can be explained by the perception of lower expectations of self-efficacy in sports where instrumentality and leadership behaviors are dominant, threats to a certain image of femininity and perceived anticipation of family-work conflict [23,21].…”
Section: Fig 3 Moderating Effect Anxiety and Decision Insecurity On T...mentioning
confidence: 99%
See 1 more Smart Citation
“…la actualidad, buscar la manera de converger entre la práctica deportiva de rendimiento y los estudios son un reto que el mundo del deporte ha comenzado a darle mayor importancia, a la vista del futuro profesional del deportista (Abelkalns et al, 2021;Mateo-Orcajada et al, 2022).…”
unclassified